2016
DOI: 10.3835/plantgenome2015.08.0074
|View full text |Cite
|
Sign up to set email alerts
|

Population Structure in the Model GrassBrachypodium distachyonIs Highly Correlated with Flowering Differences across Broad Geographic Areas

Abstract: The small, annual grass Brachypodium distachyon (L.) Beauv., a close relative of wheat (Triticum aestivum L.) and barley (Hordeum vulgare L.), is a powerful model system for cereals and bioenergy grasses. Genome-wide association studies (GWAS) of natural variation can elucidate the genetic basis of complex traits but have been so far limited in B. distachyon by the lack of large numbers of well-characterized and sufficiently diverse accessions. Here, we report on genotyping-by-sequencing (GBS) of 84 B. distach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
56
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(62 citation statements)
references
References 126 publications
(168 reference statements)
6
56
0
Order By: Relevance
“…The authors did not rule out the effects of population structure and proposed that elucidating the role of VRN2 in B. distachyon will require more in-depth genetic studies. A recent comprehensive analysis of population structure in B. distachyon collections revealed that flowering time, and not geographic origin, is indeed the major distinguishing factor between genotypically distinct clusters (Tyler et al, 2016). Our results confirm VRN2 as an important flowering regulator in the ABR6 3 Bd21 mapping population and highlight structural and expression variation between parental accessions.…”
Section: Segregation Distortion In the Abr6 3 Bd21 Populationsupporting
confidence: 71%
See 2 more Smart Citations
“…The authors did not rule out the effects of population structure and proposed that elucidating the role of VRN2 in B. distachyon will require more in-depth genetic studies. A recent comprehensive analysis of population structure in B. distachyon collections revealed that flowering time, and not geographic origin, is indeed the major distinguishing factor between genotypically distinct clusters (Tyler et al, 2016). Our results confirm VRN2 as an important flowering regulator in the ABR6 3 Bd21 mapping population and highlight structural and expression variation between parental accessions.…”
Section: Segregation Distortion In the Abr6 3 Bd21 Populationsupporting
confidence: 71%
“…Two additional QTLs on chromosomes Bd2 (qFLT3) and Bd3 (qFLT7) were detected in two environments, whereas four minoreffect QTLs (qFLT2, qFLT4, qFLT5, and qFLT8) were found in individual environments only. Two recent genomewide association studies used the natural variation found within B. distachyon germplasm to identify SNPs associated with flowering time (Tyler et al, 2016;Wilson Figure 6. Phenotype-by-genotype plot for the two major loci controlling flowering time in the ABR6 3 Bd21 mapping population.…”
Section: Segregation Distortion In the Abr6 3 Bd21 Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, two flowering-time GWAS in B. distachyon identified nine and five associated peaks, none of which overlap with the QTLs identified in this study (Tyler et al, 2016;Wilson et al, 2015). Thus, the QTL identified in our RIL population may represent rare alleles that do not surface in GWAS, or the GWAS that was conducted contains too few accessions or compounding population structures (issues that are common when conducting GWAS in in-breeding species; Weigel and Nordborg 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies in the small temperate grass model Brachypodium distachyon, which is an early diverging pooid sister to the crown pooid clade, have contributed to understanding the evolution of vernalization systems in pooids (Woods and Amasino, 2015). Like wheat and barley, B. distachyon is a long-day plant that exhibits an extensive natural variation of flowering behavior across accessions with respect to photoperiod and vernalization responses (Ream et al, 2014;Tyler et al, 2016) and has a "memory" of winter (Woods et al, 2014a). Additionally, B. distachyon contains orthologs of all of the VRN genes discovered in wheat and barley, and these genes also likely contribute to natural variation in flowering responses among different accessions of B. distachyon (Higgins et al, 2010;Woods et al, 2016Woods et al, , 2017Bettgenhaeuser et al, 2017).…”
Section: Vernalization Systems In Monocotsmentioning
confidence: 99%